Sakralitas Tua dalam Ritus Sae Toi Sanu Se’at etnik Amanuban Tengah, Nusa Tenggara Timur - Tyrsa Noviana Matau (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2021)
The purpose of this study was to analyze the meaning of Tua sacrality in the rite sae toi sanu sa'et Tua is an ethnic term Amanuban used for local drinks containing alcohol. Elderly becomes a crucial issue in the midst of society and often causes controversy from various parties who generally want to destroy old people. On the other hand, old people become sacred in the Sae Toi Sanu ritual of the Middle Amanuban ethnic group because it is a symbol of the implementation of traditional rituals. This research uses qualitative research methods with interview, observation, documentary studies and literature. An examination of the results of research using the theory of sacrality found that sacredity appears when old becomes an inseparable part of the ritual of sae toi sanu se'at, where men are prohibited from drinking old age. In addition, the old meaning is interpreted as the essence of Middle Amanuban ethnic men who are ready to provide for girls means that men have carried out the command of uis oe while at the same time having the hope that it will continue to bless by providing welfare, health, justice, fertility and prosperity for Middle Amanuban ethnicity. Uis Oe is one of the dea on earth which is believed to provide welfare, health, justice, fertility and prosperity for ethnic groups.